Dioxins levels in human blood after implementation of measures against dioxin exposure in Japan - Basilua Andre Muzembo; Miyuki Iwai-shimada; Tomohiko Isobe; Kokichi Arisawa; Masayuki Shima; Tetsuhito Fukushima; Shoji F. Nakayama (Komiyama Printing Co. Ltd, 2019)
Abstract Background Over the past few decades, the Japanese Ministry of the Environment has been biomonitoring dioxins in the general Japanese population and, in response to public concerns, has taken measures to reduce dioxin exposure. The objectives of this study were to assess the current dioxin dietary intake and corresponding body burden in the Japanese and compare Japanese dioxin data from 2011 to 2016 and 2002-2010 surveys. We also examined the relationship between blood dioxins and health parameters/clinical biomarkers. Methods From 2011 to 2016, cross-sectional dioxin surveys were conducted on 490 Japanese (242 males and 248 females, aged 49.9 ± 7.6 years) from 15 Japanese prefectures. Blood (n = 490) and food samples (n = 90) were measured for 29 dioxin congeners including polychlorinated dibenzo-para-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), and coplanar polychlorinated biphenyls (Co-PCBs) using gas chromatography coupled with high-resolution mass spectrometry. Using the 2006 World Health Organization toxic equivalence factors, the toxic equivalents (TEQs) were calculated. Clinical biomarkers and anthropometric parameters were also measured and information on lifestyle behaviours collected. Data imputations were applied to account for blood dioxins below the detection limit. Results The median (95% confidence interval or CI) blood levels and dioxin dietary intake was respectively 9.4 (8.8-9.9) pg TEQ/g lipid and 0.3 (0.2-0.4) pg TEQ/kg body weight/day. The median blood dioxin level in the 2011-2016 survey was found to have decreased by 41.3% compared to the 2002-2010 surveys. Participants who were older were found to be more likely to have higher dioxin levels. Blood dioxins were also significantly associated with body mass index, triglycerides, docosahexaenoic acid, eicosapentaenoic acid, and dihomo-gamma-linoleic acid levels in blood. Furthermore, associations between blood dioxin and dietary dioxin intake were evident in the unadjusted models. However, after adjusting for confounders, blood dioxins were not found to be associated with dietary dioxin intake. Conclusions Blood dioxin levels declined over the past decade. This study showed that the measures and actions undertaken in Japan have possibly contributed to these reductions in the body burden of dioxins in the Japanese population.